Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Berdasarkan Teori Newman dan Perilaku Pemecahan Masalah - Fahmi Abdul Halim; Puji Savvy Dian Faizati; Aulia Datul Cahyani; Anas Malik (Formosa Journal of Sustainable Research, 2022)
Researchers found several error problems experienced by students. This error can hinder the student's knowledge process, therefore it is necessary to conduct an error analysis in order to find out the error and the cause of the student's making a mistake. The research method uses a qualitative approach with the type of descriptive research. The researcher gave a story test and then examined and analyzed the test results based on the stages of Newman's error analysis. Furthermore, interviews were held with 6 subjects to reveal data or information that was not revealed in the test. The results of this study indicate that students make the most mistakes in the process skill and encoding stages. In this study also found the behavior shown by students in solving story problems: 1) DTA-Not Proficient; 2) DTA-Limited Context (without justification); and 3) DTA-Limited Context